2020
DOI: 10.1371/journal.pone.0240111
|View full text |Cite
|
Sign up to set email alerts
|

Macular microvascular parameters in the ganglion cell-inner plexiform layer derived by optical coherence tomography angiography: Vascular structure-central visual function analysis

Abstract: To investigate the relationships between global and sectoral macular vascular microcirculation parameters in the ganglion cell-inner plexiform layer (GCIPL) assessed by optical coherence tomography angiography (OCTA), and global and sectoral visual field (VF) central mean sensitivity (CMS) assessed by standard automated perimetry. Methods Fifty-four eyes with open angle glaucoma were scanned using a swept-source OCTA (Plex Elite 9000, Zeiss, Dublin, CA) and macular vascular microcirculation was measured by cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…We did not perform separate sector analysis in our dataset, we instead used the global indices of OCT, OCTA, and VF. Hollo [14], Hansen et al [15], Kwon et al [16], and Khayrallah et al [17] demonstrated that both whole and sector OCTA imaging correlates quite well with the corresponding visual function in cross-sectional studies, both in the macula and the optic nerve. The latter study, however, mentions that the diagnostic ability of vascular parameters remains lower than that of the structural parameter RNFL.…”
Section: Discussionmentioning
confidence: 97%
“…We did not perform separate sector analysis in our dataset, we instead used the global indices of OCT, OCTA, and VF. Hollo [14], Hansen et al [15], Kwon et al [16], and Khayrallah et al [17] demonstrated that both whole and sector OCTA imaging correlates quite well with the corresponding visual function in cross-sectional studies, both in the macula and the optic nerve. The latter study, however, mentions that the diagnostic ability of vascular parameters remains lower than that of the structural parameter RNFL.…”
Section: Discussionmentioning
confidence: 97%